2009
DOI: 10.1258/jrsm.2009.080211
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the epidemiology and prescribing of medication for eczema in England

Abstract: SummaryBackground The prevalence of eczema, particularly in younger children, increased substantially over the second half of the 20th century. Analysis of primary healthcare data-sets offers the possibility to advance understanding about the changing epidemiology of eczema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 22 publications
1
58
0
2
Order By: Relevance
“…The methods used to collect primary care data for the QRESEARCH database have been previously described. [9][10][11][12] In the UK, the majority of individuals resident (including children) are registered with primary care, which is free at the point of contact. Patients were included if they were registered on the first day of each year (for example, 1 January 2001) and were registered for the preceding 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…The methods used to collect primary care data for the QRESEARCH database have been previously described. [9][10][11][12] In the UK, the majority of individuals resident (including children) are registered with primary care, which is free at the point of contact. Patients were included if they were registered on the first day of each year (for example, 1 January 2001) and were registered for the preceding 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…15 In the UK the incidence of eczema has been assessed once, through a large primary care database in 2005; it was found to affect around one in nine people at some point in the year. 16 …”
Section: Background and Aimsmentioning
confidence: 99%
“…Epidemiological evidence suggests varying prevalence across countries and ethnic groups within populations 2 . It can significantly impact on the quality of life for both child and family 3 and frequently leads to healthcare consultations 4 . It is predominantly diagnosed and treated in the community 5 and managed by parents at home.…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane review, now being updated, revealed few robust trials evaluating education interventions for child eczema, with some evidence for two models, multidisciplinary teamled education and nurse-led delivery 9 . There is currently no consensus on the optimal models for supporting parents of children with eczema 4 . There is therefore a need for a systematic educational approach to enhance treatment adherence and parental support 9,10 .…”
Section: Introductionmentioning
confidence: 99%